Method of maintainance of semantic integrity of videoresource is in the infocommunication systems - Бабенко, Юрій Михайлович (Science-based technologies, 2020)
The presence of meaningful disbalance is grounded between the carrying capacities of modern infocommunication technologies and informative intensity of bit streams. Establishment is conducted that now base conception for the construction of technologies of compression presentation is a platform of JPEG. In accordance with what, it is suggested to organize further development of methods of treatment of videoresources with the use of separate component of platform of JPEG in the direction of increase of integrity of information in the conditions of providing of the required level of its availability. Development of method of exposure of meaningful segments is expounded from position of maintainance of semantic integrity of videoresource on the basis of the use of the system governed for a decision-making on information about structural-kombinatornayaproperties of mikrosegment on the brightness constituent of presentation of videoshot. System governed on authentication of segments of videoshot built taking into account the degree of their meaningfulness from position of maintainance of necessary level of integrity of objects of interest taking into account informative meaningfulness of local areas of videoshot, characterized greater homogeneity of the structural-kombinatornayaproperties. The need to create a system of comparison of indicators to estimate the amount of structural and statistical informativeness of micro-segments of images is shown. This allows one of three types of micro-segments to be identified. On the basis of which the system of rules of detection of the class of the entire segment of the video frame is based. It takes into account the importance of preserving the semantic and syntax integrity of the video frame. This makes it possible to establish with greater adequacy the informational role of each segment of the video from the point of view of its information and weight contribution to the preservation of semantic integrity and to reduce delays in processing (identification). At the same time, the informational significance of the segment takes into account its saturation with structural characteristics, which are components of objects of interest. Experimental assessments have been made of the total time delays in processing and transmitting video information in information communication systems, while maintaining the required level of reliability. The advantages of the created method are shown regarding existing methods of coding video frames using the JPEG platform.